Influence of soil-structure interaction on seismic demands in shear wall building gravity load frames. (1st November 2019) - Choinière, Mathieu; Paultre, Patrick; Léger, Pierre
Highlights: A method for computing seismic demands in gravity load resisting system is presented. Foundation movements need to be explicitly considered for soil class D and softer. Adding a single rotational spring under each core is efficient to do so. Cracked underground structure properties lead to larger demands in some elements. Gravity load frame behavior is not captured by linear analysis for soil class E. Abstract: This paper presents a complete and simple linear method, with a suitable force modification factor, to compute seismic demands in the gravity load resisting system (GLRS) of shear wall buildings including foundation movement. Based on the method first proposed by Beauchamp, Paultre and Léger in 2017, this paper compares two approaches to consider foundation movement on linear soil media such as (a) a simple rotational spring under each core and (b) a complete set of springs and dashpots. A fixed-base model using code foundation factors is also used for comparison. Springs and dashpots are assessed by modelling soil-structure interaction (SSI) with solid finite elements. Then, these approaches are evaluated for a typical 12-storey concrete shear wall building considering several nonlinear time history analyses (NLTHAs). SSI is modelled with a set of springs and dashpots, and ground motions are selected from the conditional spectrum method. NLTHAs are performed for soil classes ranging from stiff to soft, and the effect of the underground structure cracking is analysed. Analysis results show that the proposed methods are accurate in computing seismic demands in the GLRS compared to NLTHA. Foundation movements should be explicitly modelled for soil class D or softer, and underground structure cracking should be considered. For the very soft soil class E, the behaviour of the building is poorly captured in linear analysis methods; thus, nonlinear analyses are required.